Fe(III) complex of biuret-amide based macrocyclic ligand as peroxidase enzyme mimic - Panda, Chakadola; Ghosh, Munmun; Panda, Tamas; Banerjee, Rahul; Sen Gupta, Sayam (Chemical Communications, 2011)
An Fe(III) complex of a biuret-amide based macrocyclic ligand that exhibits both excellent reactivity for the activation of H(2)O(2) and high stability, especially at low pH and high ionic strength, is reported.

Crystal structure of (2S, 4R)-2-benzyl 1-tert-butyl 4-(tosyloxy)pyrrolidine-1,2-dicarboxylate, C24H29NO7S - Ghosh, Munmun; Mallick, Arijit; Diaz, David Diaz (Zeitschrift Fur Kristallographie-New Crystal Structures, 2012)
{C24H29NO7S, triclinic, P1 (no. 1)

Formation of a room temperature stable Fe-V(O) complex: reactivity toward unactivated C-H bonds - Ghosh, Munmun; Singh, Kundan K.; Panda, Chakadola; Weitz, Andrew; Hendrich, Michael P.; Collins, Terrence J.; Dhar, Basab B.; Sen Gupta, Sayam (Journal of American Chemical Society, 2014)
An Fe-V(O) complex has been synthesized from equimolar solutions of (Et4N)(2)[Fe-III(Cl)(biuretamide)] and mCPBA in CH3CN at room temperature. The Fe-V(O) complex has been characterized by UV-vis, EPR, Mossbauer, and HRMS and shown to be capable of oxidizing a series of alkanes having C-H bond dissociation energies ranging from 99.3 kcal mol(-1) (cyclohexane) to 84.5 kcal mori (cumene). Linearity in the Bell-Evans-Polayni graph and the finding of a large kinetic isotope effect suggest that hydrogen abstraction is engaged the rate-determining step.

Homogeneous water oxidation using peroxidase mimic [Fe-III(biuret-amide)] and analyte detection via signal amplification - Panda, C.; Dhar, B. B.; Ghosh, Munmun; Malvi, Bharmana; Bhattacharjee, Yudhajit; Sengupta, S. (Journal of Biological Inorganic Chemistry, 2014)

Investigation of C-C bond formation mediated by bombyx mori silk fibroin materials - Kuehbeck, Dennis; Ghosh, Munmun; Sen Gupta, Sayam; Diaz, David Diaz (ACS Sustainable Chemistry & Engineering, 2014)
The formation of C-C bonds is a prerequisite for all life on earth. Understanding the role of proteins in mediating the formation of these bonds is important for understanding biological mechanisms in evolution, as well as for designing ``green catalysts''. In this work, the ability of silk fibroin (SF) proteins to mediate selective C-C bond formation under mild conditions was comprehensively evaluated and compared between different SF-based materials and other proteins. Aqueous SF solution (ASFS), freeze-dried SF (FDSF), mesoporous SF (MPSF), and SF hydrogel (SFHG) materials were prepared and characterized by a variety of techniques including, among others, FE-SEM, ICP-OES, FT-IR, and TGA. The nitroaldol (Henry) reaction, Knoevenagel condensation, and direct aldol reaction were used as models for this study, in which the recovery and reusability of the protein was also evaluated.
Keywords: Aldol-like reactions; C-C Bond formation; Knoevenagel condensation; Proteins; Silk fibroin

Mechanism of alcohol oxidation by Fe-V(O) at room temperature - Ghosh, Munmun; Nikhil, Y. L. K.; Dhar, Basab B.; Sen Gupta, Sayam (Inorganic Chemistry, 2015)
{Selective oxidation of alcohol to its corresponding carbonyl compound is an important chemical process in biological as well as industrial reactions, The heme containing enzyme CytP450 has been known to selectively oxidize akohols to their corresponding carbonyl compounds. The mechanism of this reaction, which involves high-valent Fe-IV(O)-porphyrin(center dot+) intermediate with alcohol, has been well-studied extensively both with the native enzyme and with model complexes. In this paper, we report for the first time the mechanistic insight of, alcohol oxidation with Fe-V(O) complex of biuret TAML (bTAML), Which is isoelectronic with Fe-IV(O)-porphyrin(center dot+) intermediate form in CytP450. The oxidations displayed saturation kinetics, which allowed us to determine both the binding constants and first-order rate constants for the reaction. The K and k values observed for thel oxidation of benzyl alcohol by Fe-V(O) at room temperature (K = 300 M-1

Iron complex catalyzed selective C-H bond oxidation with broad substrate scope - Jana, Sandipan; Ghosh, Munmun; Ambule, Mayur; Sen Gupta, Sayam (Organic Letters, 2017)
The use of a peroxidase-mimicking Fe complex has been reported on the basis of the biuret-modified TAML macrocyclic ligand 'framework (Fe-bTAML) as a catalyst to perform selective oxidation of unactivated 3 degrees C-H bonds and activated 2 degrees C-H bonds with low catalyst loading (1 mol %) and high product yield (excellent mass balance) under near neutral conditions and broad substrate scope (18 substrates which includes arenes, heteroaromatics, and polar functional groups). Aliphatic C-H oxidation of 3 and 2 sites of complex substrates was achieved with predictable selectivity using steric, electronic, and stereoelectronic rules that govern site selectivity, which included oxidation of (+)-artemisinin to (+)-10 beta-hydroxyartemisinin. Mechanistic studies indicate Fe-V(O) to be the active oxidant during these reactions.